Uji Resistensi Nyamuk Culex sp. Terhadap Insektisida Golongan Piretroid (Permethrin 0,25 %) Di Kota Kupang - Alvin Haryanto Sunbanu; Julianty Almet; Diana Agustiani Wuri (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2021)
The aim of this study is to investigate the resistance status of Culex sp. as a zoonotic disease vector to pirettroid insecticide (permethrin 0,25 %) in Kupang City. The location study was conducted in Kelapa Lima and Oebobo region. The larva was randomly colected from civilians houses to than taken to laboratory to be identified and breeded. Adult mosquitos than once again identified to ensure the collected sample is indeed Culex sp. The resistance test was caried out using impregnated papers as standarized by WHO. Samples was devided into 2 group, controled and treated, 25 mosquitos each. Every region was tested with 3 repetitions. The data was collected by counting koncked down mosquitos in 1 hour time every 15 minutes and dead count after 24 hours. The result shows the resistance status of Culex sp. in Kelapa Lima is 7,06% and 12,69% in Oebobo. This shows that mosquitos in those regions is highly resistance to permethrin 0,25%.